1994
DOI: 10.1073/pnas.91.20.9426
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, expression, and in situ localization of rat intestinal cGMP-dependent protein kinase II.

Abstract: The cDNA for a membrane-associated cGMP-dependent protein kinase (cGK II) was cloned from rat intestine using reverse trnscriptase PCR and oligonucleotide primers encoding two conserved motifs of known cGMPdependent protein kinases and subsequently by screening a rat intestine cDNA library. A full-length clone encodes a protein of 761 amino acids with an estimated size of 87 kDa. Sequences of eight peptides from purified pig intestinal mucosa cGK II were found in the derived amino acid sequence of this done, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
119
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 141 publications
(124 citation statements)
references
References 24 publications
4
119
1
Order By: Relevance
“…However, recombinant mouse brain cGK II was reported to be soluble and dimeric after expression in mammalian and insect cells (5,16). In contrast, recombinant rat intestinal cGK II was found to be tightly bound to the membrane after expression in similar cell systems (4,17,18), but its oligomerization state was not established. Furthermore, the K a values for cGMP and cGMP analogs of recombinant rat intestine cGK II purified from Sf9 cells (17) differed considerably from those of recombinant mouse brain cGK II, which contained an additional N-terminal histidine tag (16).…”
mentioning
confidence: 92%
See 2 more Smart Citations
“…However, recombinant mouse brain cGK II was reported to be soluble and dimeric after expression in mammalian and insect cells (5,16). In contrast, recombinant rat intestinal cGK II was found to be tightly bound to the membrane after expression in similar cell systems (4,17,18), but its oligomerization state was not established. Furthermore, the K a values for cGMP and cGMP analogs of recombinant rat intestine cGK II purified from Sf9 cells (17) differed considerably from those of recombinant mouse brain cGK II, which contained an additional N-terminal histidine tag (16).…”
mentioning
confidence: 92%
“…The proteins in the second peak were identified by protein sequencing as C-terminal, proteolytic fragments of cGK II. The Nterminal sequences VPLDV and PPEF obtained from the 75-and the 70-kDa form, respectively, matched those of a 75-kDa cGK II fragment beginning at Val 101 and of a 70-kDa fragment starting at Pro 139 (4).…”
Section: Oligomeric State Of Recombinant Rat Intestine and Endogenousmentioning
confidence: 99%
See 1 more Smart Citation
“…Type II cGK is expressed predominantly in epithelial cells of the intestine (5-7), although it was also detected in kidney (6,8,9) and brain (6,8,10). In contrast, type I cGK, consisting of ␣ and ␤ isoforms, and shown to act as a key regulator of cardiovascular homeostasis (11,12), is not expressed in enterocytes (7).…”
mentioning
confidence: 99%
“…Localization studies have suggested a key role for a recently cloned isotype of cGMP-dependent protein kinase (cGK), designated type II, as the mediator of the cGMP-provoked intestinal Cl Ϫ secretion (5)(6)(7). Type II cGK is expressed predominantly in epithelial cells of the intestine (5-7), although it was also detected in kidney (6,8,9) and brain (6,8,10).…”
mentioning
confidence: 99%